2020
DOI: 10.21203/rs.3.rs-40089/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mental health impacts among health workers during COVID-19 in a low resource setting: a cross-sectional survey from Nepal

Abstract: Abstract Background: Health care workers exposed to COVID-19 might be at risk of developing mental health problems. The study aimed to identify factors associated with anxiety, depression and insomnia among health workers involved in COVID-19 response in Nepal. Methods: This was a cross-sectional web-based survey conducted in between April 26 to May 12, 2020. A total of 475 health workers participated in the study. Anxiety and depression were measured using 14-item Hosp… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
39
3
3

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(50 citation statements)
references
References 40 publications
(64 reference statements)
5
39
3
3
Order By: Relevance
“…The overall pooled point estimates of prevalence for anxiety varied between 8% and 91%, which was reported by 73 studies [ [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [28] , [29] , [30] , 32 , 34 , 35 , [37] , [38] , [39] , [42] , [43] , [44] , [45] , [46] , 48 , 49 , 51 , [53] , [54] , [55] , [56] , [57] , 62 , [64] , [65] , [66] , [67] , [71] , [72] , [73] , [74] , [75] , [76] , [77] , [78] , [79] , [80] , [81] , [82] , [83] , [84] , [85] , [86] , [87] , [88] , [89] , [90] , [91] , [92] , [93] , [94] , [95] , [96] , [97] , [98] , [99] ,…”
Section: Resultsmentioning
confidence: 99%
“…The overall pooled point estimates of prevalence for anxiety varied between 8% and 91%, which was reported by 73 studies [ [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [28] , [29] , [30] , 32 , 34 , 35 , [37] , [38] , [39] , [42] , [43] , [44] , [45] , [46] , 48 , 49 , 51 , [53] , [54] , [55] , [56] , [57] , 62 , [64] , [65] , [66] , [67] , [71] , [72] , [73] , [74] , [75] , [76] , [77] , [78] , [79] , [80] , [81] , [82] , [83] , [84] , [85] , [86] , [87] , [88] , [89] , [90] , [91] , [92] , [93] , [94] , [95] , [96] , [97] , [98] , [99] ,…”
Section: Resultsmentioning
confidence: 99%
“…A study in China also showed that nurses experienced more unfavorable mental health outcomes than other health staff ( Khanal et al, 2020 ; Lai et al, 2020 ; Maunder et al, 2004 ). Of note, poor mental health in healthcare workers will affect the quality of the health care provided ( Khanal et al, 2020 ; Brooks et al, 2018 ; Maharaj et al, 2019 ). Therefore, hospital leadership should pay special attention to the mental well-being of their employees, especially nurses, as the mismanagement of their mental health can lead to dire public health consequences.…”
Section: Discussionmentioning
confidence: 99%
“…In their study, Khanal et al reported that inadequate isolation precautions were significantly associated with signs of anxiety and depression among healthcare workers ( Khanal et al, 2020 ). A shortage in preventive measures, such as insufficient PPE, can render the work environment dangerous, leading to a feeling of insecurity and vulnerability to the infection.…”
Section: Discussionmentioning
confidence: 99%
“…Quarantine, social isolation and travel restrictions had negatively impacted the mental health of people who have COVID-19 and their families. A few preliminary studies have shown the psychological issues such as stress, anxiety, depression, insomnia among the general population (13)(14)(15) as well as frontline health workers (16,17). A study by Gupta, Mehra (16) conducted among 150 health workers showed that 38 % of the healthcare workers on COVID-19 duty in Nepal suffered anxiety and/or depression (16).…”
Section: Healthcare Impactmentioning
confidence: 99%
“…A study by Gupta, Mehra (16) conducted among 150 health workers showed that 38 % of the healthcare workers on COVID-19 duty in Nepal suffered anxiety and/or depression (16). Another online survey conducted among 475 health workers showed that 41.9% of health workers had symptoms of anxiety, 37.5% had depression symptoms and 33.9% had symptoms of insomnia (17). Incidents of stigmatization and social discrimination of healthcare workers, people who have COVID-19 and their families were also reported in Nepal during the lockdown (18,19).…”
Section: Healthcare Impactmentioning
confidence: 99%